The Concurrent Validity and Reliability of Single Leg Squat Among Physically Active Females with and without Dynamic Knee Valgus - Nazatul Izzati Jamaludin; Farhah Nadhirah Aiman Sahabuddin; Nur Syahmina Rasudin; Shazlin Shaharudin (International Journal of Sports Physical Therapy)
# Background